2020
DOI: 10.1167/iovs.61.13.30
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Spheroids and Axon Pathology Identified in Amyotrophic Lateral Sclerosis

Abstract: To determine whether patients with amyotrophic lateral sclerosis (ALS) show retinal axon pathology. METHODS. Postmortem eyes from 10 patients with ALS were sectioned and compared with 10 age-matched controls. Retinal sections were evaluated with periodic acid Schiff and phosphorylated (P-NF) and nonphosphorylated (NP-NF) forms of neurofilament with SMI 31 and 32 antibodies. Spheroids identified in the retinal nerve fiber layer were counted and their overall density was calculated in central, peripheral, and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 84 publications
(107 reference statements)
1
12
0
Order By: Relevance
“…Interestingly, one study also showed an increased thickness in certain areas of the retina [ 180 ], suggesting alterations in axonal transport, protein aggregation, and neuroinflammation as possible explanations. Supporting this finding, in post-mortem studies, a significantly greater number of PAS-positive spheroids has been found in RNFL, especially in the peripapillary region [ 198 ]. The increased presence of phosphorylated neurofilaments in these spheroids could be explained by a special vulnerability of the long axons to axonal transport deficits.…”
Section: Involvement Of the Visual System In Alsmentioning
confidence: 69%
“…Interestingly, one study also showed an increased thickness in certain areas of the retina [ 180 ], suggesting alterations in axonal transport, protein aggregation, and neuroinflammation as possible explanations. Supporting this finding, in post-mortem studies, a significantly greater number of PAS-positive spheroids has been found in RNFL, especially in the peripapillary region [ 198 ]. The increased presence of phosphorylated neurofilaments in these spheroids could be explained by a special vulnerability of the long axons to axonal transport deficits.…”
Section: Involvement Of the Visual System In Alsmentioning
confidence: 69%
“…In addition, in most of the ALS patients, the NP-NF signal was increased in the RNFL and IPL. Nevertheless, there was no significant correlation of these retinal spheroids and axon pathology with the clinical characteristics of the ALS patients (age at death, gender, disease duration, mode of disease onset, revised ALS functional rating scale, and rate of disease progression) [115].…”
Section: Histopathological Studies In Als and Retinal Spheroids And A...mentioning
confidence: 84%
“…There is only one study that focused on this important pathological mechanism in the retina [115]. This study analyzed retinal sections of postmortem eyes from ALS patients with periodic acid Schiff (PAS) and phosphorylated (P-NF) and nonphosphorylated (NP-NF) forms of neurofilament (NF), compared with age-matched controls.…”
Section: Histopathological Studies In Als and Retinal Spheroids And A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Axons connect the nervous system with the rest of the body to ensure its proper function and the interaction with the outside world. However, any insult to the nervous system such as trauma, ischemia, neurodegeneration, and demyelination [ 2 ] leads to permanent impairment of motor, sensory, cognitive, and automatic nerve functions [ 3 5 ]. Thus, understanding mechanisms involved in nervous system repair is crucial not only for the neuroscience field but also for public health.…”
Section: Introductionmentioning
confidence: 99%